Hop extracts to provide functional and tunable haze to bright beer and design specialty styles - Bissoonauth, Tony; Fisher, Gillian; Hall, Dave; Wilson, Colin; Oliveira, Pedro (BrewingScience, 2021)
HOP SPECIALMany of today's beers are designed to impart a pronounced haziness which is viewed as a highly desirable visual characteristic by the consumer, particularly among the specialty beer categories. In classic beers, haze is normally associated with a lack of filtration and/or chemical stabilization. As such, most of the turbidity lacks standardization over its storage time as seen in commercial hazy beers, which causes technical processing challenges for brewers when formulating new styles. Also, other ingredients used to add haze can be detrimental in terms of processing, final beer organoleptic quality and beer shelf-life. To that end, a hop extract, denominated Hop Haze Fraction (HHF), has been developed, characterized, and further explored for its potential application in bright beer to impart functional haze which could emulate unfiltered styles. HHF was spiked and assessed for stability in representative bright lager beers, as well as in malt test medium, using IPA, Ale and Wheat beers as references. Its impact on the overall beer taste was assessed. Results have shown that most beers displayed a high degree of haze stability over time, when dosed with HHF. It has also contributed towards synergies with beer base boosting the hop aroma, juicy character, and bitterness perception. The amount of haze imparted was tunable, and the degree of haze stability was affected by a combination of multiple factors such as the beer composition and its processing conditions. Beers spiked with HHF have shown increased haze stability and outperformed references. This work shows that HHF has the potential to be used as a post-fermentation and liquid dosing solution to standardize haziness into a bright beer matrix while maintaining the desirable beer taste quality parameters. In addtion showing promissing technical benefits for the brewhouse optimization, such as reproducibility, tunability, and maintaining hops naturalness status.